Science as a Resource for Territorial and Tourism Development of Mountainous Areas of Chilean Patagonia - Fabien Bourlon; Yannick Vialette; Pascal Mao (Revue de Géographie Alpine)
The region of Aysén, in Chilean Patagonia, is an isolated natural mountainous area, which relies on science for its tourist and territorial development. Project leaders are promoting specific scientific research underway in the territory. Science is mobilized as a resource in the creation of products, recreational and educational activities, commercial or non-profit. These initiatives are carried out by research centers, universities, entrepreneurs, and non-governmental organizations and reveals that the acquisition and sharing of scientific knowledge creates local dynamics that contribute to the tourism and territorial development. By nature, the mountain environment is a resource and laboratory for scientific research. It is also a favorable environment for citizen science and an ideal support for mediation and scientific interpretation. Scientific tourism initiatives promote a diversification and an added value that increases territorial assets and the attractiveness of an isolated but evolving area.